ATP-Induced IL-1β Specific Secretion: True Under Stringent Conditions - Stoffels, Monique; Zaal, Ruben; Kok, Nina; van der Meer, Jos W. M.; Dinarello, Charles A.; Simon, Anna (Frontiers in Immunology, 2015)
Interleukin-1β is a potent proinflammatory cytokine, of which processing and secretion are tightly regulated. After exposure to various stimuli, mononuclear phagocytes synthesize the inactive precursor (pro-IL-1β), which is then cleaved intracellularly by caspase-1 and secreted. A widely used method for in-vitro secretion of IL-1β employs LPS-primed human peripheral blood monocytes. Subsequently, adenosine triphosphate (ATP) is added to the cells in order to trigger the P2X7 receptor resulting in processing and secretion of mature IL-1β. However, it is often reported that secretion is due to cytotoxic effects of ATP with P2X7 receptor-activation-related cell death. We have challenged this concept and demonstrate IL-1β specific secretion, since there is no increase in cell death and IL-1α and IL-18 are not released in the same cultures. More importantly we show that these conclusions can only be drawn under stringent experimental conditions.